Gain Power Through No Power: Effectiveness of China's Roles in Conflict Resolution between Saudi Arabia and Iran Long-Standing Dispute - Aula Wiji Kinasih, Raden Safinatul; Surwandono (Review of International Relations, 2023)
This research will discuss about the role of China as a conflict resolver between Saudi Arabia and Iran that just happened in March 2023. The two Gulf states decided to work toward settling their differences in accordance with a set of international principles and two bilateral agreements reached in 1998 and 2001 after seven years of military and diplomatic animosity. A deal to restore diplomatic ties between Riyadh and Tehran was announced in a joint statement by Saudi Arabia, Iran, and China on March 10 and Beijing become the place these intense negotiations take place. This shows how big China roles and influence in the middle east, thus bringing the researcher to a question what strategy they used. This research uses qualitative research method by collecting data from former journal and research. This research found that China goal behind taking the role is to strengthen their stances through soft balancing strategy. Thus, this research will explain more about the strategy and the use of China diplomacy approach that compliment it, making it possible for China to gain power without exerting one at all.